2021
DOI: 10.3389/finsc.2021.765570
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Increased Homing Flight Duration and Altered Gene Expression in the Brain of Honey Bee Foragers After Acute Oral Exposure to Thiacloprid and Thiamethoxam

Abstract: Neonicotinoids as thiamethoxam and thiacloprid are suspected to be implicated in the decline of honey bee populations. As nicotinic acetylcholine receptor agonists, they disturb acetylcholine receptor signaling in insects, leading to neurotoxicity and are therefore globally used as insecticides. Several behavioral studies have shown links between neonicotinoid exposure of bees and adverse effects on foraging activity, homing flight performance and reproduction, but the molecular aspects underlying these effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Moreover, phytochemicals in nectar and pollen can also negatively interact with honeybee energy metabolism 28 . Changed expression of cox5a , cox5b and cox17 in mixed-aged foragers after exposure to spinosad also shows the possible effects of pesticides on energy balance in bees 24 . In addition, exposure of mixed-aged foragers to the fungicide chlorothanolin changed the expression of cox5a , cox5b and cox17 25 .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Moreover, phytochemicals in nectar and pollen can also negatively interact with honeybee energy metabolism 28 . Changed expression of cox5a , cox5b and cox17 in mixed-aged foragers after exposure to spinosad also shows the possible effects of pesticides on energy balance in bees 24 . In addition, exposure of mixed-aged foragers to the fungicide chlorothanolin changed the expression of cox5a , cox5b and cox17 25 .…”
Section: Discussionmentioning
confidence: 92%
“…However, ilp-1 level can drop while foraging continuous, making the link to behavior ambiguous 53 , 54 . Various pesticides altered the expression of ilp-1 in the brain of foragers among them thiacloprid, thiamethoxam, cypermethrin, spinosad and chlorothanolin 24 27 . In contrast to the data presented here, which show a downregulation of ilp-1 after exposure to 0.06 ng/bee CPF, a study by Fent and colleagues showed an induction of ilp-1 after exposure to 0.6 ng/bee CPF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, recent research has suggested that thiacloprid causes transcriptional changes in gene associated with mitochondria, which in turn affects metabolism and energy allocation in the bee brain [ 16 ]. The alterations in the energy metabolism in the brain can translate to various physiological and behavioural changes [ 9 , 16 , 27 ] and may be one reason for the reduced homing capacity, as well as for the reduced learning performance, after the lower exposure.…”
Section: Discussionmentioning
confidence: 99%